Antimicrobial, remineralization, and infiltration: advanced strategies for interrupting dental caries - Yang Qingyi; Li Fan; Ye Yangyang; Zhang Xu (Medical Review)
Dental caries, driven by plaque biofilm, poses a major oral health challenge due to imbalance in mineralization and demineralization. The primary objective in caries management is to maintain biofilm homeostasis while facilitating the repair and regeneration of dental hard tissues, thus restoring both structural integrity and functionality of affected teeth. Though antimicrobial and remineralization approaches haven shown promise, their standalone utilization without concurrent bacterial control or rebalancing lacks an integrated strategy to effectively arrest caries progression. Furthermore, according to the principles of minimally invasive dentistry, treatment materials should exhibit high permeability to ensure optimal sealing of demineralized tooth surfaces. The concept of interrupting dental caries (IDC) has emerged as a holistic approach, drawing upon extensive research encompassing three pivotal techniques: antibacterial strategies, remineralization therapies, and infiltration mechanisms, all of which are indispensable components in combating the progression of dental caries. In this review, we provide a comprehensive overview of the mechanisms and applications of antibacterial, remineralization, and infiltration technologies within the context of caries management. Additionally, we summarize advanced materials that align with the IDC concept, aiming to offer valuable insights for designing next-generation materials adept at preventing or halting caries progression efficiently.